Traumatic Cardiac Injury: Ventricular Perforation Caught on CT. (12th June 2016) - Golshani, Behrad; Dong, Paul; Evans, Scott
Abstract : Myocardial rupture is a rare imaging diagnosis given its clinical severity and high mortality. Early findings should be promptly communicated to the trauma service to ensure immediate intervention. We present a rare case of blowout perforation of the right ventricle which was prospectively diagnosed on computed tomography (CT) leading to emergent operative repair. The patient subsequently survived and was discharged after a lengthy hospital course.